2002
DOI: 10.1080/09593332508618414
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity Analysis of Stabilization Pond System Design Parameters

Abstract: Two stabilization pond systems are examined. A sensitivity analysis is undertaken, aimed at investigating the influence of the pond depths on stabilization pond surface area and pond volume for the specific combination of temperature, wastewater characteristics and effluent requirements. The dependencies are presented in a functional form, allowing for the graphical solution of the unit pond volume, area, and hydraulic residence time as a function of the respective pond depths. Based on these graphs, designers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…According to Pearson (1986, 1987), Mara et al (1992) and Economopoulou and Tsihrintzis (2002), the design of SPs is sensitive to pond temperatures. In the winter, the mean daily pond temperature is warmer by 2-3 1C than the mean daily air temperature.…”
Section: Sizing and Performance Criteria Of Natural Wastewater Treatmmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Pearson (1986, 1987), Mara et al (1992) and Economopoulou and Tsihrintzis (2002), the design of SPs is sensitive to pond temperatures. In the winter, the mean daily pond temperature is warmer by 2-3 1C than the mean daily air temperature.…”
Section: Sizing and Performance Criteria Of Natural Wastewater Treatmmentioning
confidence: 99%
“…The sizing process for SP systems is based on the theory by Pearson (1986, 1987), and Mara et al (1992), and step-bystep procedures and nomographs developed by Economopoulou and Tsihrintzis (2002Tsihrintzis ( , 2004. Economopoulou and Tsihrintzis (2002) employed the design equations and methodology proposed by Pearson (1986, 1987), and Mara et al (1992) for SP systems comprising one anaerobic, one facultative and an optimum number of maturation ponds, and tested the performance of these systems in wastewater treatment through sensitivity analysis. The results showed that conventional designs for high performance during winter offer very limited capacity gains in summer without significant pond oversizing.…”
Section: Introductionmentioning
confidence: 99%
“…According to Mara and Pearson [15], [16], Mara et al [17] and Economopoulou and Tsihrintzis [8], the design of stabilization ponds is sensitive to pond temperatures. In the winter, the mean daily pond temperature is warmer by 2 to 3ºC than the mean daily air temperature.…”
Section: Analyzing the Variablesmentioning
confidence: 99%
“…The final step in the present work was the estimation of the required area for stabilization pond systems based on the mean minimum monthly temperatures of record, the population of each municipality and the required wastewater effluent discharge criteria, according to the methodology proposed by [8], [9]. The required areas of each municipality were compared to the suitable areas that resulted from the GIS analysis, in order to accept stabilization pond systems as a solution to wastewater treatment problem for each one of the examined municipalities.…”
Section: The Boolean Evaluation --Use Of Gis In Siting Stabilization mentioning
confidence: 99%
“…Anaerobic treatment followed by stabilization ponds or lagoons as secondary treatment offers a simple and economical alternative of treatment of distillery wastewaters with the aim of using the final effluent as soil conditioner. Stabilization ponds have been widely studied by many authors and successfully applied [9][10][11][12][13][14][15][16][17]. They are one of the most effective and widely used methods for wastewater purification in developing countries especially in hot climates because of the high values of natural radiation and temperatures usually achieved in these tropical countries.…”
Section: Introductionmentioning
confidence: 99%